INTEGRATING PRESENTATION, PRACTICE, AND PRODUCTION STAGES IN FOREIGN LANGUAGE TEACHING: A PEDAGOGICAL FRAMEWORK FOR SKILL DEVELOPMENT - Kuchkarova Mukhabbat Yigitaliyevna (Bright Mind Publishing, 2026)
This study explores the integration of Presentation, Practice, and Production (PPP) stages as a comprehensive pedagogical framework for skill development in foreign language teaching. While the PPP model has often been associated with structured, form-focused instruction, this research reconceptualizes it as a flexible and communicatively oriented framework capable of supporting balanced language skill development. The study adopts a quasi-experimental design involving undergraduate EFL learners in a higher education context. Over an eight-week instructional period, the experimental group received instruction based on an integrated PPP framework, while the control group followed traditional grammar-oriented teaching methods. Quantitative data from pre- and post-speaking assessments, combined with classroom observations and learner perception surveys, were analyzed using inferential statistical techniques. The findings reveal significant improvements in communicative competence, fluency, and grammatical accuracy among students exposed to the integrated PPP framework (p < 0.001). Moreover, learner motivation and classroom engagement increased notably during the production stage, where authentic communicative tasks were incorporated. The results suggest that effective integration of presentation, practice, and production stages can bridge the gap between structural accuracy and communicative fluency. The study contributes to contemporary discussions on foreign language pedagogy by demonstrating that PPP, when applied flexibly and interactively, aligns with modern communicative approaches and fosters sustainable skill development in higher education settings.
Keywords: Presentation–Practice–Production (PPP); foreign language teaching; communicative competence; skill development; EFL pedagogy; learner motivation; classroom methodology; higher education.